2021
DOI: 10.2196/23795
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine Use and Health-Related Concerns of Patients With Chronic Conditions During COVID-19: Survey of Members of Online Health Communities

Abstract: Background It has been widely communicated that individuals with underlying health conditions are at higher risk of severe disease due to COVID-19 than healthy peers. As social distancing measures continue during the COVID-19 pandemic, experts encourage individuals with underlying conditions to engage in telehealth appointments to maintain continuity of care while minimizing risk exposure. To date, however, little information has been provided regarding telehealth uptake among this high-risk popula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
43
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 21 publications
7
43
1
Order By: Relevance
“…Less than one half of them (45%) anticipated using telemedicine after the end of the pandemic. These findings are consistent with Sousa et al [ 35 ], who found that “patients were satisfied with communication with providers; however, one half evaluated the online visit as inferior when compared to in-person visits”, and also with Horrell et al [ 36 ], who found that 43% of the participants preferred to return to face-to-face, in-person meetings, whenever this would be possible in the post-COVID-19 era.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Less than one half of them (45%) anticipated using telemedicine after the end of the pandemic. These findings are consistent with Sousa et al [ 35 ], who found that “patients were satisfied with communication with providers; however, one half evaluated the online visit as inferior when compared to in-person visits”, and also with Horrell et al [ 36 ], who found that 43% of the participants preferred to return to face-to-face, in-person meetings, whenever this would be possible in the post-COVID-19 era.…”
Section: Discussionsupporting
confidence: 88%
“…Women tend to search for more healthcare information than men and use telemedicine more, as per Horrell et al [36] who found that 50% of the women used telemedicine compared with 43% of the men, and expressed greater satisfaction with telemedicine [43]. On many occasions, it is the women in the family who are responsible for overall family health, so they are the ones who contact the physicians on behalf of other family members [45].…”
Section: Discussionmentioning
confidence: 99%
“…A literature search for a comparable international investigation identified a US-based study that utilized an online survey in May 2020, which recruited 2210 respondents with chronic diseases, with 49% reporting engaging in telehealth. 17 Additionally, similar to our findings, it was noted that in their patient sample, the aging population was less likely to benefit from telehealth services.…”
Section: Discussionsupporting
confidence: 88%
“…RenderX almost all families have access to the internet or a telephone in Wuhan and Shanghai [51], and quota sampling enhanced the representativeness of our sample to minimize selection bias, we are aware that our sample is not a probabilistic random sample of residents from the two cities. Similar to other online surveys [52], the response rate was below 10% in our study. Second, there may be recall bias due to the self-reported data.…”
Section: Xsl • Fosupporting
confidence: 75%